Fact learning in complex arithmetic—the role of the angular gyrus revisited. Issue 9 (30th April 2016) - Bloechle, Johannes; Huber, Stefan; Bahnmueller, Julia; Rennig, Johannes; Willmes, Klaus; Cavdaroglu, Seda; Moeller, Korbinian; Klein, Elise
Abstract: In recent theoretical considerations as well as in neuroimaging findings the left angular gyrus (AG) has been associated with the retrieval of arithmetic facts. This interpretation was corroborated by higher AG activity when processing trained as compared with untrained multiplication problems. However, so far neural correlates of processing trained versus untrained problems were only compared after training. We employed an established learning paradigm (i.e., extensive training of multiplication problems) but measured brain activation before and afte training to evaluate neural correlates of arithmetic fact acquisition more specifically. When comparing activation patterns for trained and untrained problems of the post‐training session, higher AG activation for trained problems was replicated. However, when activation for trained problems was compared to activation for the same problems in the pre‐training session, no signal change in the AG was observed. Instead, our results point toward a central role of hippocampal, para‐hippocampal, and retrosplenial structures in arithmetic fact retrieval. We suggest that the AG might not be associated with the actual retrieval of arithmetic facts, and outline an attentional account of the role of the AG in arithmetic fact retrieval that is compatible with recent attention to memory hypotheses. Hum Brain Mapp 37:3061–3079, 2016 . ©2016 Wiley Periodicals, Inc.